The Urgency of Community Participation and Empowerment in Corporate Social Responsibility (CSR) Programs: A Case Study in Riau Province, Indonesia - Firdaus, M. Johar; Suwaryo, Utang; Deliarnoor, Nandang Alamsah; Rahmatunnisa, Mudiyati (Journal of Ecohumanism, 2025)
Community empowerment is crucial for poverty alleviation, allowing communities to develop their potential and strengthen their power. However, government funding is limited, leading to the need for Corporate Social Responsibility (CSR) programs. In Riau Province, Indonesia, CSR implementation is not optimal, resulting in a poverty rate of 8.42%. The research uses a qualitative method with a case study approach to analyze the situation. CSR programs should focus on community empowerment and partnership, using principles like democratic, transparent, accountable, and responsive. However, issues such as involving the community in program development, focusing on community economic development, lack of community economic empowerment, lack of sustainability, lack of synergy with the government, and assistance provided hinder community empowerment.